Evaluasi Ekonomi Parsial antara Pemberian Terapi Rivaroxaban dan Terapi Kombinasi (Unfractionated Heparin + Warfarin) untuk Pengobatan Trombosis Vena Dalam pada Pasien Kanker di Rumah Sakit Kanker Dharmais - Syari, Wirda; Nadjib, Mardiati; Ranuhardy, Dody (UI Scholars Hub, 2020)
Based on previous studies, rivaroxaban therapy has several advantages compared to combination therapy (UFH+warfarin) for the treatment of deep vein thrombosis (DVT). However, the use of rivaroxaban in Dharmais Cancer Hospital is still low. This partial economic evaluation study aims to analyze cost and outcome of rivaroxaban therapy and combination therapy (UFH+warfarin) for DVT treatment in cancer patients at the Dharmais Cancer Hospital during 2016 – 2018. Data collection was done using cohort-retrospective and individual unit of analysis. Due to limited number of patient treated with rivaroxaban therapy within 3-6 months, we estimated the cost and outcome related to patients who were successfully treated in one month. The outcome was the intermediate outcome, i.e length of stay, recovery, and the occurrence of bleeding. The cost was calculated based on hospital perspective including drugs, laboratory tests, procedures, as well as the administrative and accommodation costs. The results showed that patients with rivaroxaban therapy were not admitted to inpatient care, 40% of patients were recovered from DVT, and none of the patients experienced bleeding. The average cost of rivaroxaban therapy to reach the expected outcome was Rp 8,824,791.00. The study also showed that patients with combination therapy (UFH+warfarin) had a hospital length of stay between 8 to 14 days, 46% of patients were recovered from DVT, and none of the patients experienced bleeding. The average cost of combination therapy (UFH+warfarin) to reach the expected outcome was Rp 13,201,698.00.